Chemical Literacy Ability in Gender Perspective on Acid-Base Material - Saputri, Erlinda Novriani; Laksono, Pandu Jati; Wigati, Indah (PAEDAGOGIA, 2023)
Research on chemical literacy skills from a gender perspective on acid-base materials has been conducted at SMA Y in Lahat District. This study aimed to determine students' chemical literacy skills from a gender perspective in acid-base material. This type of research is descriptive research with a qualitative approach. The subjects of this study were 28 students of class XI MIPA 1 at SMA Y in Lahat Regency, with 14 male and 14 female students. The instruments in this study were chemical literacy test questions in the form of descriptions and interview guidelines. The results of this study indicate that the chemical literacy ability of SMA Y students in the Lahat Regency is, on average, 56% in the low category. The difference in chemical literacy based on gender for male students is 54%, and for female students is 59%. The chemical literacy of female students is better than male students, with a difference of 5%, and is included in the low category. Female students were better able to answer questions that explained the concept of acids and bases, while male students were better able to answer questions on acid-base calculations